Sutureless and glue free limbal conjunctival auto graft for primary pterygium surgery - Sharma, MK (Nepalese Journal of Ophthalmology, 2013)
Nepal J Ophthalmol 2013; 5(9):139-140 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7845